(3TQM GdJUQja GdYRjs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J (B793 (3g`s ((3eMeO TajY Hf OYhGOGQs)
(3ChdgG (B:s
(3HSe Gddg (B... (3deG QCjJ GdeNJUQ GdPj UfYg GdEeGe YHO GdhgGH Hf EHQGgje GdRfLGfj (B.. (3eNJUQG jfWhj Ydi eHGMK TQjaI hjMJhj Ydi bhGYO dWjaI SfM dj Cf CTQMg TQMG jPdd (B...s
(3BNQgG (B:s
..(3gPG aj GdKdGKj GdeLQO GdPj dG JGA ajg hCeG ZjQg aGdfhY efg cGdeQI HdG aQb aj GddaX hGdaGQb GdbQGFjf GdNGQLjI Jbhd QMeJg QMeI hGMOI ddeQI dWjaI Ch fMhgG ddfhY (B... (3hcPG GdHhGbj (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\ 219s
(3cTa GdXfhf (B2\1139s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas